2008
DOI: 10.1097/bsd.0b013e318157d382
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of ProDisc-C Failure Strength With Cervical Bone Mineral Content and Endplate Strength

Abstract: This study demonstrates the utility of a preoperative QCT scan in predicting the failure stress of the cervical endplate before total disc replacement. This information may potentially decrease early complications of device subsidence or endplate fracture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
17
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 15 publications
0
17
0
Order By: Relevance
“…19,42 The two-part resin was viscous when mixed and therefore did not leach or interdigitate with the endplate. The intention was to level the superior surface prior to biomechanical testing to provide a uniform interface with the materials testing machine without affecting the internal structure of the vertebra.…”
Section: Specimen Preparation and Bone Density Measurementmentioning
confidence: 99%
See 2 more Smart Citations
“…19,42 The two-part resin was viscous when mixed and therefore did not leach or interdigitate with the endplate. The intention was to level the superior surface prior to biomechanical testing to provide a uniform interface with the materials testing machine without affecting the internal structure of the vertebra.…”
Section: Specimen Preparation and Bone Density Measurementmentioning
confidence: 99%
“…Factors influencing the limits included the weight of a human head ($50 N) for the minimum limit and the published failure load of the implant-endplate interface for the maximum limit (range: 754-2,238 N). 17,19,42 Since the intent was to examine the implant-endplate interface under cyclic loading, a maximum limit of 250 N was selected to allow a factor of safety with respect to the published ultimate failure loads.…”
Section: Specimen Preparation and Bone Density Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 1 [2,20,21,26,[28][29][30]. C3D4 is the tetrahedral solid element with 19 four nodes, C3D8 is the hexahedral solid element with eight nodes, C3D10 is the 20 decahedral with ten nodes, T3D2 is the truss element with two nodes in the ABAQUS 21 software, and the total numbers of nodes and elements are 377,877 and 330,648. The two types of artificial disc prostheses were implanted at the C5-C6 level [26], 5 where CDR is most frequently performed ( Figure 2F).…”
mentioning
confidence: 99%
“…36 ProDisc-C (Synthes Spine) is one of the cervical artificial discs in current use, and very promising clinical results have been reported for this device. 3,4 However, recent clinical studies have reported vertebral body split fractures associated with single and multilevel cervical arthroplasty using the ProDisc-C prostheses.…”
mentioning
confidence: 99%